Impact of liver fibrosis and nodules formation on hemodynamics in young adults after total cavopulmonary connection. A magnetic resonance study - Chaloupecký, Václav; Jičínská, Denisa; Tomek, Viktor; Materna, Ondřej; Gebauer, Roman; Poruban, Rudolf; Antonová, Petra; Adla, Theodor; Štefánek, Matěj; Illinger, Vojtěch; Kotaška, Karel; Janoušek, Jan (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The aim of this study was to analyze the relation between the hepatic fibrosis markers, liver morphology and hemodynamics assessed by magnetic resonance imaging (MRI) after total cavopulmonary connection (TCPC). Methods: Adult patients after TCPC performed in childhood between 1993 and 2003 are the subjects of this observational study. The follow-up protocol consisted of clinical and echocardiographic examination, liver elastography, cardiopulmonary exercise test, MRI hemodynamics and liver morphology assessment and direct enhanced liver fibrosis (ELF) test. Results: The cohort consisted of 39 patients (46% female) with a median age at study 26 (IQR 23 28) years and interval from TCPC 21 (IQR 20 – 23) years. There was no correlation between ELF test and any MRI variables, but procollagen III amino-terminal peptide (PIIINP), a single component of ELF test, correlated significantly with ventricular end-diastolic volume (r = 0.33; p = 0.042) and inferior vena cava flow (r = 0.47; p = 0.003). Fifteen (38%) patients with liver nodules had compared to other 24 patients higher end diastolic volume (ml/m2) 102.8 ± 20.0 vs 88.2 ± 17.7; p = 0.023 respectively. PIIINP correlated significantly with inferior vena cava flow (r = 0.56; p = 0.030) and with end diastolic volume (r = 0.53; p = 0.043), but only in patients with liver nodules. Conclusions: Gradual progression of liver fibrosis, particularly hepatic arterialization caused by liver nodules formation, increases inferior vena cava flow and subsequent ventricular volume overload may further compromise single ventricle functional reserve in adult patients after TCPC.